Uncommon Leadership 11 ways the greatest leaders lead - Newman, Ben (Per Capita Publishing, 2021)
In Uncommon Leadership, performance coach and motivational consultant Ben Newman takes you inside the minds and hearts of eleven exceptional individuals: athletes, coaches, CEOs, entrepreneurs, and others whose unrelentingly high performance has made them not only the best in their fields but also unquestioned leaders in sports, business, and life. Ben breaks it down, honing in on the core qualities that drive these trailblazers to push for the best in themselves and others, every single day.
Keywords: Leadership